Pengaruh Putaran Mesin dan Suhu Gas Buang Terhadap Konsumsi Bahan Bakar Pada Mesin Induk Kapal KM Sangiang - Rangga Pradana Parikesid; Antonius Edy Kristiyono; Shofa Dai Robbi; Monika Retno Gunarti; Agus Prawoto (LPPM Institut Pendidikan Nusantara Global, 2026)
Efficient fuel use is a major focus of the shipping industry in reducing operational costs and environmental impacts. This study analyzes the effect of engine speed (X1) and exhaust gas temperature (X2) on fuel consumption (Y) in a ship's main propulsion engine. This study aims to determine the effect of engine speed and temperature on fuel consumption in a ship's main propulsion engine. The research method used is quantitative to determine the effect of engine speed and exhaust gas temperature on fuel consumption of a ship's main propulsion engine. The research data sources were obtained from ship's logbooks and engine manuals, the data were analyzed using statistical methods to determine the relationship between engine speed and exhaust gas temperature on ship's fuel consumption. The results of the study indicate a significant relationship between engine speed (RPM) and exhaust gas temperature variables on fuel consumption of the main propulsion engine. Where engine speed and exhaust gas temperature tend to increase fuel consumption of the ship's main propulsion engine. The implication of this study is the importance of controlling engine speed and exhaust gas temperature to optimize the efficiency of fuel consumption of the ship's main propulsion engine.